Water Permeability of Pervious Concrete Is Dependent on the Applied Pressure and Testing Methods - Yinghong Qin; Haifeng Yang; Zhiheng Deng; Jiang He (Advances in Materials Science and Engineering)
Falling head method (FHM) and constant head method (CHM) are, respectively, used to test the water permeability of permeable concrete, using different water heads on the testing samples. The results indicate the apparent permeability of pervious concrete decreasing with the applied water head. The results also demonstrate the permeability measured from the FHM is lower than that from the CHM. The fundamental difference between the CHM and FHM is examined from the theory of fluid flowing through porous media. The testing results suggest that the water permeability of permeable concrete should be reported with the applied pressure and the associated testing method.